2022
DOI: 10.1152/ajplung.00458.2021
|View full text |Cite
|
Sign up to set email alerts
|

IL10 trains macrophage profibrotic function after lung injury

Abstract: Cx3cr1+ monocyte-derived macrophages (moMacs) are recruited to tissues after injury and are known to have pro-fibrotic effects, but the cell-cell interactions and specific pathways that regulate this polarization and function are incompletely understood. Here we investigate the role of moMac-derived Pdgfa in bleomycin-induced lung fibrosis in mice. Deletion of Pdgfa with Cx3cr1-CreERT2 decreased bleomycin-induced lung fibrosis. Among a panel of in vitromacrophage polarizing stimuli, robust induction of Pdgfa w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…Pro-fibrotic exposures (pustulan and scleroglucan) also increased BAL cell counts and macrophage concentrations. Macrophages are increasingly recognized for their role in development of pulmonary fibrosis (6264) with excessive M2 macrophages playing a pro-fibrotic role (65). Macrophage response to BDGs has been demonstrated to be independent of the classic BDG receptors Dectin-1 and TLR2 (66, 67); because Dectin-1 is not independently responsible for Th2 sensitization in a BDG (+house dust mite) mouse model (55), macrophage recruitment and signaling might explain the fibrotic phenotype observed after exposure to these BDGs.…”
Section: Discussionmentioning
confidence: 99%
“…Pro-fibrotic exposures (pustulan and scleroglucan) also increased BAL cell counts and macrophage concentrations. Macrophages are increasingly recognized for their role in development of pulmonary fibrosis (6264) with excessive M2 macrophages playing a pro-fibrotic role (65). Macrophage response to BDGs has been demonstrated to be independent of the classic BDG receptors Dectin-1 and TLR2 (66, 67); because Dectin-1 is not independently responsible for Th2 sensitization in a BDG (+house dust mite) mouse model (55), macrophage recruitment and signaling might explain the fibrotic phenotype observed after exposure to these BDGs.…”
Section: Discussionmentioning
confidence: 99%
“…A major emerging theme is the role of moMacs, which support a range of pathologic phenotypes in multiple disease models ( 29 , 30 ). Lung fibrosis is no exception, with monocyte-lineage cells being shown to be associated with poor outcomes in multiple clinical cohorts ( 31 ) and in mouse models including our own prior work showing a pro-fibrotic effect of moMacs ( 1 3 , 6 ). This pathologic effect of macrophages has been proposed to be related to macrophage-derived factors that both support fibroblast growth and lead to fibroblast activation, including TGFβ, PDGF, and other secreted factors ( 4 6 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent work profiled the fibrotic phase of lung injury at the single-cell level, revealing a subset of Cx3cr1+ macrophages that localize to clusters of activated fibroblasts and exert a profibrotic effect ( 3 ). With respect to the profibrotic mechanisms of these macrophages, one emerging view is that they activate surrounding fibroblasts by secreting cytokines and growth factors, such as TNFα, TGFβ, and PDGF ( 2 6 ). However, the full repertory of signals deriving from macrophages is not known.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of IL10RA upregulation on macrophages in glomerulopathy has not been well illustrated. One study on lung injury revealed high expression of IL10RA in macrophages and its induction of fibroblast activation after injury ( Bhattacharyya et al, 2022 ). VSIG4, also referred to as the complement receptor of the immunoglobulin (CRIg) superfamily, encodes a protein of v-set and immunoglobulin domain-containing 4 that is exclusively expressed on tissue-resident macrophages ( He et al, 2008 ) and is regarded as a new regulator of immunity.…”
Section: Discussionmentioning
confidence: 99%